Pengaruh Edukasi Melalui Media Puppet Show dan Flashcard Mengenai Jajanan Aman di SDN Wanasari 12 Cibitung - oleifera, Syifa kharisma; Prasetya, Guntari (JGK: Jurnal Gizi dan Kesehatan, 2024)
Diarrhea is an infectious disease in children caused by the consumption of unsafe snacks. Based on the results of supervision conducted by BPOM RI found that 4% of food sold in the school environment contained hazardous materials. Low knowledge is one of the causes of unsafe snacks consumption in school children, providing nutrition education is one solution in increasing children's knowledge about safe snacks consumption. This study used an experimental method with a quasi-experiment research design with two groups pretest and posttest to determine the effect of nutrition education through puppet show media and flashcards on knowledge about safe snacks in elementary school children at SDN Wanasari 12 Cibitung. In statistical analysis, the Wilcoxon test was conducted to determine the increase in knowledge about safe snacks in the experimental group and the control group p-value = 0.0001